1, 4-addition reaction of 5H-oxazol-4-ones to vinyl ketones catalyzed by chiral guanidines. Issue 1 (1st January 2015) - Morita, Akane; Misaki, Tomonori; Sugimura, Takashi
Graphical abstract: Abstract: In this Letter, a chiral guanidine-catalyzed 1, 4-addition reaction of 5 H -oxazol-4-ones to vinyl ketones is described. The 1, 4-addition reaction proceeded with a high enantioselectivity using 5 H -oxazol-4-ones, substituted with a 3-chloro-5-methylphenyl group, as pronucleophiles and a newly developed chiral guanidine as a catalyst. The optimized reaction conditions were also effective in achieving excellent enantioselectivity in the 1, 6-addition to dienones. Subsequent solvolysis of the 1, 4-addition adduct yielded the corresponding α-hydroxy-5-oxocarboxylates.